Market Structure, Technology Spillovers, and Persistence in Productivity Differentials - Yin-Wong Cheung; Antonio I. Garcia Pascual (Center for Economic Studies and ifo Institute (CESifo), 2001)
Using data from 11 main manufacturing industries in 17 OECD countries, this paper empirically investigates the determinants of cross-country differences in the persistence of productivity differentials Specifically, we focus on the effects of product market structure and technology diffusion. It is found that the manufacturing industries display a wide range of convergence rates. Consistent with theories, the persistence of productivity differentials is found to be positively correlated with the price-cost margin and the intra-industry trade index - the proxies for market monopolistic behavior. The proxies for tecnology diffusion, however, do not exhibit consistently significant effect. Among the conditioning macro variables, productivity convergence appears to be enhanced by human capital but deterred by government spending.
Keywords: 330; Total factor productivity; convergence; market structure; technology diffusion